Dispersion of red blood cells in microchannels : a confocal micro-PTV assessment - Lima, Rui A. (2008)
Blood in large arteries may be treated as a homogenous fluid from a macroscopic prospective. However, in reality blood is a suspension of deformable cells in viscous fluid plasma. In microcirculation, which comprises the smallest arteries and veins, the flow behavior of individual blood cells and their interactions provide the microrheological basis of flow properties of blood at a macroscopic level. Hence, in microcirculation it is fundamental to study the flow behavior of blood at cellular level. Several studies on both individual and concentrated RBCs have already been performed in the past. However, all studies used conventional microscopes and also ghost cells to obtain visible trace RBCs through the microchannel. The present study is concerned in providing further insights into the microscale blood flow behavior through microchannels by applying an emerging optical technique known as confocal micro-PIV/PTV. The technique consists of a spinning disk confocal microscope, high speed camera and a diode-pumped solid state (DPSS) laser combined with a single particle tracking (SPT) software (MtrackJ). Detailed measurements on the motions of RBCs were measured at different haematocrits (Hct) and the correspondent radial dispersion coefficient was determined.